The impact of unresolved magnetic spots on high-precision radial velocity measurements. Issue 3 (27th July 2020) - Lisogorskyi, M; Saikia, S Boro; Jeffers, S V; Jones, H R A; Morin, J; Mengel, M; Reiners, A; Vidotto, A A; Petit, P
ABSTRACT: The Doppler method of exoplanet detection has been extremely successful, but suffers from contaminating noise from stellar activity. In this work, a model of a rotating star with a magnetic field based on the geometry of the K2 star ϵ Eridani is presented and used to estimate its effect on simulated radial velocity (RV) measurements. A number of different distributions of unresolved magnetic spots were simulated on top of the observed large-scale magnetic maps obtained from 8 yr of spectropolarimetric observations. The RV signals due to the magnetic spots have amplitudes of up to 10 m s −1, high enough to prevent the detection of planets under 20 Earth masses in temperate zones of solar-type stars. We show that the RV depends heavily on spot distribution. Our results emphasize that understanding stellar magnetic activity and spot distribution is crucial for the detection of Earth analogues.